TERAPI MUSIK UNTUK MENURUNKAN TINGKAT ANSIETAS HOSPITALISASI PADA ANAK PALEMBANG 2021: TERAPI MUSIK UNTUK MENURUNKAN TINGKAT ANSIETAS HOSPITALISASI PADA ANAK PALEMBANG 2021 - ARLY FEBRIANTI, DESY ANGGRAINI (STIKES Hesti Wira Sriwijaya, 2022)
ABSTRAKLatar Belakang Ansietas di definisikan sebagai suatu keadaan emosional yang terdiri dari perasaan ketegangan, ketakutan, gugup dan khawatir dengan aktivitas atau gairah dari system saraf otonom, dimana ansietas terdiri dari dua komponen yaitu komponen situasi / keadaan dan sifat. Tujuan Penelitian untuk mengetahui manfaat terapi musik dalam menurunkan tingkat asnisetas Hospitalisasi MetodePenelitian ini merupakan design penelitian dengan menggunakan sumber literaturyang berbentuk buku, jurnal, Hasil Penelitian : Penelitian ini menunjukkan bahwa terdapat perbedaan yang signitif terhadap tingkat ansietas sebelum dan susudah diberikan terapi musik . Kesimpulan : terapi musik mampu mengatasi penurunantingkat ansietas yang terjadi pada anak.Kata Kunci : Ansietas, Hospitalisasi, Terapi Musik, AnakABSTRACTBackground : Anxiety is defined as an emotional situation consisting of feelings, fear,nervousness and worry with the activity or arousal of the autonomic nervous system, where anxiety consist of two components which are situation and state Purpose: This literature study aims to obtain an overview of the effect of music theraphy to reduce anxiety of the effect of music therapy to reduce anxiety levels in hospitalized children Methods: This study used a literature review study using literary sources in the form of books, scientific articles, especially published ones. By doing a search through googlescholar, Researchgate, published from 2016-2020. Results: The results of this studyindicate that there are significant differences in the level of anxiety before and after being given music theraphy. Conclusion: Music therapy is able to overcome the decrease inanxiety levels that occur in shildren. With music therapy can reduce anxiety levels in children. It is hoped that this literature study can add insight to knowledge for nurses and parents that musictherapy can reduce anxiety levels in hospitalized children.Keywords : Anxiety, Hospitalization, Therapy Music, Child